RIGHT OF ACCESS ON UNDERGROUND LAND DEVELOPMENT: GUIDANCE FROM SINGAPORE AND AUSTRALIA - Najah Inani Abdul Jalil; Ain Husna Mohd Arshad (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In 1990, the creation of underground land is created in the National Land Code. The scarcity of land especially in urban areas has pushed the traditional horizontal land development into vertical land development. Apart from transportation purposes, it is suitable for recreational, storage, and service utility purposes. Within this development, it attracts questions such as how to reconcile the right of surface and underground landowners as the law has allowed the ownership of underground land to be independent and separate from the surface owner. In governing the relationship between the surface and the underground landowners, the provision of access, support, and protection are regulated under the express condition in the document of title. This paper explores the concept of the right of support in Malaysia and the requirement for its application. This paper uses the doctrinal method where statutory provisions, cases, legal articles are examined. In discussing this topic, the practice in Singapore and Australia is compared, and it is suggested in regulating the relationship between surface and underground landowners, the creation of easement to be adopted with the compensation to be awarded to the burdened land.